2016
DOI: 10.1007/s11121-016-0716-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Couples’ Processes of Change in the Context of SASA!, a Violence Against Women and HIV Prevention Intervention in Uganda

Abstract: There is now a growing body of research indicating that prevention interventions can reduce intimate partner violence (IPV); much less is known, however, about how couples exposed to these interventions experience the change process, particularly in low-income countries. Understanding the dynamic process that brings about the cessation of IPV is essential for understanding how interventions work (or don’t) to reduce IPV. This study aimed to provide a better understanding of how couples’ involvement with SASA!—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Indeed, Fielding-Miller and Dunkle’s (2017) research of transactional sex in Swaziland found that love was protective against IPV, in that women who reported having sex with a partner for reasons other than love or affection (such as poverty, money, hunger, fear of abandonment, or violence) had increased odds of emotional, physical, and sexual violence. Starmann and colleagues (2016) assessed processes of change among couples exposed to the SASA! IPV prevention programme in Uganda and suggested that SASA!’s focus on core relationship values such as love, respect and trust was essential to reducing violence and improving relationship quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Fielding-Miller and Dunkle’s (2017) research of transactional sex in Swaziland found that love was protective against IPV, in that women who reported having sex with a partner for reasons other than love or affection (such as poverty, money, hunger, fear of abandonment, or violence) had increased odds of emotional, physical, and sexual violence. Starmann and colleagues (2016) assessed processes of change among couples exposed to the SASA! IPV prevention programme in Uganda and suggested that SASA!’s focus on core relationship values such as love, respect and trust was essential to reducing violence and improving relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…The SASA! intervention in Uganda found that as IPV and conflict in relationships decreased, love and trust increased (Starmann et al, 2016). In a study of Ugandan HIV sero-discordant couples, some reported that love motivated them to continue the relationship and adhere to pre-exposure prophylaxis (PrEP) (Ware et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The findings speak to the value of interviewing both partners of couples, which is relatively uncommon in IPV prevention research, although there have been recent calls for this (Davis et al 2012;Wadsworth and Markman 2012;Starmann et al 2017). The findings further identify the importance of interviewing curriculum implementers, perspectives that are often neglected by impact evaluations.…”
Section: Discussionmentioning
confidence: 77%
“…Other studies have found engaging couples can be more effective than separating men and women to equip change in relationships and reduce IPV (El-Bassel and Wechsberg 2012; Starmann et al 2017). Mixed-group educational efforts can model equitable gender relations, mobilise men's care for the women and girls in their lives, and enhance their accountability to women (Anderson and Whiston 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation